Pengaruh Lama Fermentasi Jerami Jagung Menggunakan Kapang Trichoderma Harzianum terhadap Kandungan Serat dan Kecernaan In Sacco - Suryadi Suryadi; M. Afdal; Fachroerrozi Hoesni; Jahtera Manalu (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Corn straw is an alternative feed from agricultural waste that can be widely used by farmers as ruminant feed. This study aims to determine the fiber content and in sacco digestibility of corn straw fermented with Trichoderma harzianum. The design of this experiment was Completely Randomized Design with 5 treatments and 4 replications. The samples were treated with 5 length of fermentation time, namely: 0 (control) , 4, 8, 12 and 16 days. Nylon bag technique was applied to evaluate the sample degradation. Corn straw that has been ground to a size of 2 mm, taken as much as 5-6 g, then put into a nylon bag and incubated in the cattle rumen for 72 hours. The results showed that corn straw fermentation using Trichoderma harzianum increased the content of NDF, ADF and the degradation of ADF but dit not increased the NDF and hemicellulose digestibility. In conclusion, the best fermentation time is 12-16 days under aerobic conditions.